Perioperative strategies for renal protection - Md Ralib, Azrina (2021)
Acute Kidney Injury (AKI) is common, occurring in 10 to 30% perioperatively, and this can lead to increased morbidity and mortality. Currently, there is no therapeutic intervention available, hence perioperative renal protection strategies are important to reduce the consequences of AKI. Current consensus of AKI definition was based on serum creatinine and urine output criteria as in the Kidney Disease in Improving Global Outcome (KDIGO) 2012 guideline. However, both have limitations in the perioperative settings, and this present a diagnostic challenge that precludes good interventional study that impede development of novel pharmacologic therapy. Newer biomarkers offer a better diagnostic opportunity and provide more insight of functional verses injury paradigm, however, is limited by cost and availability. It is important for us to understand the pathophysiology and risk factors for early identification of high-risk patients, so that appropriate strategies could be carefully implemented. Risk assessment prior to surgery is crucial to optimize strategies to prevent AKI and to determine which patients might require more intense monitorization after surgery. The KDIGO guideline proposes to implement a bundle of preventive measures in patients at high risk for AKI. Application of this bundle in high risk patients identified by new biomarker has been shown to reduce overall AKI incidence in cardiac and non-cardiac surgery. Appropriate strategies to deliver optimal amount and type of fluid management perioperatively is important to prevent AKI. Various pharmacological therapies has been studied, of these dexmedetomidine and statin has shown a promising result.